2017
DOI: 10.1038/nphys4252
|View full text |Cite
|
Sign up to set email alerts
|

Self-peeling of impacting droplets

Abstract: Whether an impacting droplet 1 sticks or not to a solid surface has been conventionally controlled by functionalizing the target surface 2-8 or by using additives in the drop 9,10 . Here we report on an unexpected self-peeling phenomenon that can happen even on smooth untreated surfaces by taking advantage of the solidification of the impacting drop and the thermal properties of the substrate. We control this phenomenon by tuning the coupling of the shorttimescale fluid dynamics-leading to interfacial defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 34 publications
4
55
0
Order By: Relevance
“…Furthermore, as a result of the random motion, the temperature of the hot surface tends to be non‐uniform, which in turn causes an unwanted stress distribution. [ 3 ] Thus, it is essential to concentrate or confine all the impacting droplets onto a localized hotspot region for efficient thermal management.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, as a result of the random motion, the temperature of the hot surface tends to be non‐uniform, which in turn causes an unwanted stress distribution. [ 3 ] Thus, it is essential to concentrate or confine all the impacting droplets onto a localized hotspot region for efficient thermal management.…”
Section: Figurementioning
confidence: 99%
“…Droplet manipulation is a ubiquitous phenomenon in various natural processes and biological processes such as selfcleaning, [1][2][3][4] drag reduction, [3,[5][6][7][8] and microfluidics. [9][10][11][12][13] As one of the key aspects for droplet manipulation, [7,[14][15][16][17][18] the directional transportation of liquid droplets has aroused great interest due to its importance in applications including water collecting, [19][20][21] anti-icing [16,22,23] and materials transportation.…”
Section: Introductionmentioning
confidence: 99%
“…During freezing after impact release stresses and effects of surface tension may built up, and flattened splats may detach from the substrate [2]. Very recently, for liquid tin droplets impinging at fairly low velocity, de Ruiter et al reported so-called self-peeling when examining smooth, flat, horizontally oriented surfaces of various materials with different thermal conductivity and effusivity [9]. We have also examined such conditions where tin drops do not stick to the substrate due to self-peeling, and observed even a further step in some cases, namely receding and self-contraction of already spread-out pancake-like tin splats.…”
Section: Introductionmentioning
confidence: 99%
“…Self-peeling of droplets is expected to be less pronounced on oxidic materials [9]. To analyze the dependence of the adhesion of tin drops on the layer material, we study bare and strongly oxidized silicon wafers as well as Mo/Si coated mirrors without cap layer and with protective zirconium nitride (ZrN) or zirconium oxide (ZrO 2 ) cap layers.…”
Section: Introductionmentioning
confidence: 99%